Auditor Independence and Its Influence on Accounting Behavior: A Systematic Literature Review - Wan Fachruddin; Haflah Furqan (Journal of Creative Power and Ambition (JCPA), 2026)
Auditor independence is a fundamental pillar of corporate governance that safeguards the quality of financial reporting and mitigates the risk of reporting manipulation. This study aims to map the latest empirical evidence on the influence of auditor independence on corporate accounting behavior. Adopting a Systematic Literature Review approach guided by the PRISMA reporting framework, this study thoroughly examines 30 reputable scientific articles indexed in the Scopus database, published within the last five years (2021–2026). The search strategy employed the keywords 'auditor independence', 'accounting behavior', 'earnings management', and 'reporting quality' combined with Boolean operators. The main findings indicate that the relationship between auditor independence and accounting behavior is complex; independence does not exert a single linear effect but is strongly shaped by critical mediating and moderating variables, including audit tenure, audit fees, client pressure, firm ethical culture, and auditor gender diversity. This synthesis reveals patterns of consensus and theoretical debate regarding the effectiveness of oversight mechanisms. The article contributes theoretically by enriching the discourse on audit ethics and offers practical guidance for regulators in formulating more adaptive supervisory policies, as well as serving as a strategic reference for auditors seeking to enhance professionalism and objectivity amid the complexities of modern business.